Prevalence of Computer Vision Syndrome (CVS) and its associated risk factors among IIUM Kuantan Undergraduates - Ruslan, Siti Nur Liyana; Zamli, Zaitunnatakhin (2022)
Introduction: Excessive computer use has increased among workers and students, particularly during the COVID-19 pandemic. Computer vision syndrome (CVS) has previously impacted many Malaysian undergraduates. However, International Islamic University Malaysia (IIUM), Kuantan has no prior or current data on CVS among their university students, raising the question of whether students are experiencing CVS symptoms when using computers, particularly during online teaching and learning. Methods: A cross-sectional study was conducted at IIUM Kuantan to determine the prevalence of CVS and its associated risk factors among undergraduates. A convenience sampling method was employed to recruit study participants, and data was collected using a self-administered questionnaire. The prevalence of CVS prevalence was calculated and its association with ergonomics and non-ergonomic risk factors was determined using statistical analysis. Results: The data showed that the CVS prevalence was 69.3%, with a higher prevalence among female and Kulliyyah of Medicine students than other Kulliyyahs. Most CVS cases were classified as mild, with tired eyes (89.9%), neck and shoulder pain (88.7%), and headache (73.4%) among the most reported symptoms. The severity of the CVS symptoms was found to be significantly inversely correlated with ergonomics practices (r= - 0.137, p= 0.034). Conclusion: Despite good ergonomics practices reported by the participants, a weak correlation between these factors raises the question of whether the participants have a correct practice of computer ergonomics. Hence, the present findings suggest that training in good computer ergonomics practices is necessary.